We are going to be pals! - Teague, Mark (Beach Lane Books, an imprint of Simon & Schuster Children's Publishing Division, 2023)
A talkative cattle egret explains to a rhinoceros that in addition to having a symbiotic relationship, they also have a friendship built on communication, kindness, and a respect for boundaries.